Environment Improvement, Creative Economic Development, And Children’s Education in Banjarsari Village - Rita Ambarwati; Putri Permatasari; Inzani Nur Saadah; Indrianingsih Mawardi; Silmida Faujiah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
The implementation team of Community Service Activities in Banjarsari Village, Buduran District, carried out three work programs, including the Environment, Creative Economy, and Educational Programs. The problems faced are caring attitude toward the environment, forums for entrepreneurship around Banjarsari Village, and Children's passive education. The goal is to build motivation and the community to create a calm environment while developing the creative economy and increasing awareness of the importance of education in early childhood. Then problem-solving in this research can be done by providing knowledge, understanding, and behavioral training.